Ergonomics study in Quick Response Manufacturing (QRM) automotive workstation environment to overcome employee complaints - Nelfiyanti, Nelfiyanti; Nik Mohd Zuki, Nik Mohamed; M. F. F., Ab. Rashid (Springer Link, 2021)
The assembly line is an important process in producing a complete car unit before the product is checked and delivered to the consumer. Assembly workers during working hours are affected by work position, workload, placement of components and aids during the process and equipment used in assisting heavy work processes. Work positions with non-ergonomic workloads impact the disability and musculoskeletal complaints (MSD) of workers. The purpose of this study is to identify the ergonomic risks of assembly workers. Analytical methods using the Nordic Body Map (NBM) and QRM principles were used in this study. The results of the analysis of the level of complaints of workers’ MSD during the work were obtained for the categories of not sick (NS) 27.94%, slightly sick (SS) 36.76%, sick (S) 29.69% and very sick (VS) 5.6%. The most dominant complaints about S and VS complaints were shoulders, arms, back, waist, buttocks, wrists and hands. MSD complaints that employees feel are in the middle category with an average score of 64 points which means immediate remedial action is needed. Using the time-focused QRM principle, improvements in work procedures and designing ergonomic tools are needed to minimize MSD complaints that impact working hours faster, and there is no overtime